Sensation transference from plateware to food: The sounds and tastes of plates - Chen, Y; Woods, A; Spence, C (Intellect, 2018)
We report two experiments designed to extend the well-known Bouba/Kiki effect to the case of an unusual set of commercially produced plateware, and further to assess the influences of these plates on the expected taste of a dessert based on the theory of crossmodal correspondences. The results demonstrate that plates having a smoother circumference are more likely to be matched to ‘Bouba’, while those with a pointier circumference are more likely to be matched to ‘Kiki’ instead, thus demonstrating the typical Bouba/Kiki effect. Importantly, the shape and colour of the plates modulated people’s ratings of the expected taste and liking of the ice cream/sorbet displayed on them. Specifically, the colour of the plate induced a general effect on the expected tastes that were consistent with the white-sweet and black-bitter associations, and the higher expected liking of the ice cream/sorbet was attributed to the higher colour contrast between the food and plate. The shape of the plate modulated ratings of expected liking for the chocolate ice cream and the expected sweetness of the lemon sorbet. Finally, colour and shape conjointly modulated how sour the lemon sorbet was expected to taste. These results provide relevant insights for those chefs, restaurateurs and Instagrammers wishing to optimize the plateware for specific dishes.